Methodology of Projects from Children's Literature: an approach to Early Childhood Education from the point of view of students and teachers (Research, Society and Development, 2023)
The project methodology conceives the student as an active subject in the learning process considering subjective, historical and cultural aspects of the students. This work aims to present an approach through the methodology of projects for Early Childhood Education, and to reflect on the perception of the teachers involved in the activity, as well as the contribution to the learning process of students at this stage. It is a participatory research that involved five classes (two kindergarten and three preschool). Data were collected through access to the field diary prepared by the teachers and through the use of a questionnaire. The results indicate that the project methodology provides a collective and interdisciplinary work among teachers and allows the student to actively participate in the construction of their learning. Therefore, it is concluded that the project made it possible to transform the school into a place of exchanges and formation of protagonism for teachers and students.